Closed-Loop Brain Devices in Offender Rehabilitation: Autonomy, Human Rights, and Accountability - Ligthart, Sjors (Cambridge quarterly of healthcare ethics, 2021)
The current debate on closed-loop brain devices (CBDs) mainly focuses on their use in a medical context; possible criminal justice applications have only received incidental scholarly attention. Unlike in medicine, in criminal justice, CBDs might be offered on behalf of the State and for the purpose of protecting security, rather than realizing healthcare aims. It would be possible to deploy CBDs in the rehabilitation of convicted offenders, similarly to the much-debated possibility of employing other brain interventions in this context. Although such use of CBDs could in principle be consensual, there are significant differences between the choice faced by a criminal offender offered a CBD in the context of criminal justice, and that faced by a patient offered a CBD in an ordinary healthcare context. Employment of CBDs in criminal justice thus raises ethical and legal intricacies not raised by healthcare applications. This paper examines some of these issues under three heads: autonomy, human rights, and accountability.